BRAF V600E immunohistochemistry as a useful tool in the diagnosis of melanomas with ambiguous morphologies and immunophenotypes. (1st December 2022) - Rothrock, Aimi T.; Hameed, Nadia; Cho, Woo Cheal; Nagarajan, Priyadharsini; Ivan, Doina; Torres‐Cabala, Carlos A.; Prieto, Victor G.; Curry, Jonathan L.; Aung, Phyu P.
Abstract: We report three melanoma cases in which BRAF V600E immunohistochemistry (IHC) was valuable for diagnosis. Patient 1: In a patient with a history of primary melanoma on the chest and metastatic melanoma to right breast after undergoing multiple local and systemic therapies, a lung metastasis exhibited chondroid differentiation, aberrant myofibroblastic marker expression, and rare pancytokeratin positivity, without melanocytic marker expression. Patient 2: After targeted and immunotherapy for primary melanoma on the scalp as well as regional and distant metastatic melanoma, an omental metastasis showed CDX2‐positive glandular structures that were negative for melanocytic markers. It was initially misdiagnosed as primary gastrointestinal adenocarcinoma. Patient 3: A patient with history of melanoma showing epithelioid morphology on the right thigh presented with multiple soft tissue nodules on skin, lymph nodes and internal organs after being lost to follow‐up for 4 years. A biopsy specimen from the right thigh showed spindled cells with scattered pancytokeratin cocktail positivity and ambiguous staining for melanocytic markers. For melanomas with ambiguous morphologies and/or immunophenotypes in each of the three patients, BRAF V600E expression by IHC was maintained in both primary and metastatic melanoma specimens examined. These cases highlight the utility of BRAF V600E IHC in the diagnosis of melanoma.